Critical Quantitative Research: Foreclosing Criticality within Education - Davis, Bradley; Saunders, Daniel (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2022)
The purpose of this conceptual paper is to engage with the idea of criticality, specifically as performed by higher education researchers that espouse a critical quantitative approach. We contend there are many inherent hazards, ethical commitments, and contradictions that come with engaging in critical quantitative inquiry. Chief among the hazards and contradictions is the outright foreclosure of criticality as theorized by the very foundational principles cited in the extant conceptualizations of critical quantitative inquiry. To date, and as we will demonstrate through our review of relevant research, critical quantitative inquiry in education has largely failed to establish these recognitions. After examining the primary works on the topic, we offer a discussion of ways to recapture some of the positive potential we find in the early writings on critical quantitative inquiry.